Functional Outcomes for Meniscal Allograft Interposition Arthroplasty of the Hand - McCullough, Meghan C. (Plast Reconstr Surg Glob Open, 2021)
BACKGROUND: Osteochondral defects of the carpometacarpal (CMC), metacarpophalangeal (MCP), and proximal interphalangeal (PIP) joints often necessitate arthrodesis or arthroplasty. Meniscal allograft has been used for large joint resurfacing, but its application to smaller joints is less well understood. We propose its use for hand joint resurfacing as an off-the-shelf alternative to address osteochondral defects and restore articular function. METHODS: Thirty-one patients with osteoarthritis of the CMC, MCP, or PIP joints underwent arthroplasty with meniscal allograft. Patient demographics and operative information were recorded. Preoperative Disability of the Shoulder, Arm, and Hand, Wong Baker pain, grip and pinch strength, and range of motion were compared to postoperative scores at 6 weeks, 6 months, and 1 year. RESULTS: Twenty-three women and 8 men, mean age 62.8 years, underwent 39 joint reconstructions, including CMC (n = 26), thumb MP (n = 2), thumb IP (n = 2), digit MP (n = 2), and digit PIP (n = 7). At 1 year, mean Disability of the Shoulder, Arm, and Hand scores decreased from 41.3 to 15.6 (P < 0.001) and pain scores from 6.9 to 1.0 (P < 0.001). Grip strength increased from 38.1 to 42.9 (P = 0.017) and radial and palmar abduction from 43.1 to 49.2 (P = 0.039) and 43.7 to 51.6 (P = 0.098), respectively. There were no complications related to the meniscus. CONCLUSIONS: Meniscal allograft represents an alternative to arthrodesis which obviates the need for a donor site and avoids many of the complications inherent to synthetic alternatives. Our early results demonstrate its successful use to reduce subjective pain and disability scores, improve objective strength measures, and maintain range of motion.